Narrative Semiology of Personal Brokerage in Jababr Jamal Gharib's Novel "The Time of Balqis's Crying" (Raparin Journal of Humanities (RJH), 2024)
Narrative semiology has evolved with the trends and directions of semiology. Philip Hammon's theoretical view of narrative personality is one of the foundations of narrative expansion and the elements of narrative have a role and influence in guiding critical and narrative research. This paper is entitled "Narrative Semiology of Personal Brokerage in Jababr Jamal Gharib's Novel The Time of Balqis's Crying". It is an attempt to practice a new theory of semiology within the foundation of narrative personality, how are that foundation and the system of personality signs embodied in the narrative text? In coordination with the reader, he presents the personal meaning through signifier and is mindful of its semantic dimension.